2021
DOI: 10.1590/1806-9282.20210265
|View full text |Cite
|
Sign up to set email alerts
|

Trends in teenage pregnancy in Brazil in the last 20 years (2000-2019)

Abstract: OBJECTIVE:The aim of this study was to evaluate the frequency of teenage pregnancy in all Brazilian regions and states in the period of 2000-2019 among two age groups, namely, 10-14 and 15-19 years old, and correlate it with the human development index. METHODS:A cross-sectional study was performed by using the data from the Live Birth Info System from the National Health System's database. RESULTS:The percentage of live births from teenage mothers (age 10-19 years) in Brazil decreased by 37.2% (i.e., 23.4 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
1
5
0
4
Order By: Relevance
“…Despite the decrease of 37.2% in the frequency of adolescent pregnancy in the past years 12 , repeated pregnancy does not occur in the same way. It can be verified that in Brazil, between 2015 and 2019, there was no significant decrease in repeated pregnancy.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the decrease of 37.2% in the frequency of adolescent pregnancy in the past years 12 , repeated pregnancy does not occur in the same way. It can be verified that in Brazil, between 2015 and 2019, there was no significant decrease in repeated pregnancy.…”
Section: Discussionmentioning
confidence: 88%
“…Advanced maternal age is a risk factor in the later period, but is not significant in the earlier period. This shift may owe something to the dramatic decline in teenage pregnancy in Brazil in the last 20 years (Monteiro et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…There was a reduction of 37.2% (23.4% in 2000 to 14.7% in 2019) and 48 births per 1,000 adolescents aged 15-19 years in 2019 (in 2000, the fertility rate in the age group 15-19 years was 81/1,000). It is observed that the LB percentage is inversely proportional to the human development index (HDI), because only the Southeast and South regions presented indicators below the country's average (38.2 and 39‰, respectively) 2 . However, the numbers of adolescent pregnancy are still very high in relation to developed countries, and there is great regional inequality within the country.…”
Section: Introductionmentioning
confidence: 99%